Pengembangan Buku Ajar Berbasis Augmented Reality (AR) Menggunakan Assemblr Apps pada Tema 9 “Menjelajah Angkasa Luar” Kelas VI Sekolah Dasar - Lilis Novia Santi; Nuriman; Kendid Mahmudi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2022)
This study aims to determine the results of the validity and effectiveness of the textbooks. The research used is the research and development research of the Borg and Gall model with 10 stages of research, namely preliminary research, planning and development, initial product design development, product validation, initial product revision, use trials, product development revisions, effectiveness trials, final product, dissemination. The results of data analysis for sixth grade students at SDN 1 Grajagan, SDN 4 Grajagan, and SDN 8 Grajagan during validation showed the average percentage of validity was 91.72 percent so that it was in the very valid category. The effectiveness of the product is seen based on student responses and learning outcomes tests. The results of the data during the limited trial showed a positive response to the product by 88.4 percent. Meanwhile, the results of the product effectiveness trial at SDN 1 Grajagan, SDN 4 Grajagan, SDN 8 Grajagan were 80 percent, 72.22 percent, 90 percent respectively. This shows that Augmented Reality (AR) based textbooks are very feasible and effective to use when learning. Penelitian ini bertujuan mengetahui hasil validitas dan efektivitas dari buku ajar yang dikembangkan. Penelitian yang digunakan ialah penelitian pengembangan Research and Development model Borg and Gall dengan 10 tahapan penelitian, yaitu penelitian pendahuluan, perencanaan dan pengembangan, pengembangan desain produk awal, validasi produk, revisi produk awal, uji coba penggunaan, revisi produk pengembangan, uji coba keefektifan, produk final, Dissemination. Hasil analisis data siswa kelas VI SDN 1 Grajagan, SDN 4 Grajagan, dan SDN 8 Grajagan saat validasi menunjukkan persentase rata-rata tingkat kevalidan sebesar 91,72 persen sehingga masuk kategori sangat valid. Keefektifan produk dilihat berdasarkan respons siswa dan tes hasil belajar. Hasil data saat uji coba terbatas menunjukkan respons positif terhadap produk sebesar 88.4 persen. Sedangkan hasil uji coba keefektifan produk di SDN 1 Grajagan, SDN 4 Grajagan, SDN 8 Grajagan secara berturut-turut ialah 80 persen, 72,22 persen, 90 persen. Hal tersebut menunjukkan buku ajar berbasis Augmented Reality (AR) sangat layak dan efektif digunakan saat pembelajaran.